The Effects of Back Massage on Dysmenorrhoea in Adolescents - Suazini, Esa Risi; Humaeroh, Lina (Poltekkes Kemenkes Surakarta, 2024)
Background: The incidence of dysmenorrhoea worldwide is 92%, and primary dysmenorrhea cases are more than half. Dysmenorrhea interferes with products, decreases quality of life, increases health costs, and increases dependent drug consumption, all of which adversely affect health. This study aimed to determine the effect of back massage on primary dysmenorrhea in adolescents. Methods: Quasi-experimental one-group design research. Samples were determined incidentally and obtained from adolescents. Data analysis using the paired sample t-test. Results: There is an effect between back massage and dysmenorrhea (p-value 0.000). Back massage can reduce 80% of primary dysmenorrhea. Conclusion: We need to socialize back massages as an alternative to primary dysmenorrhea therapy in the community.